Conflict of Law Regarding Natural Resource Management in Indonesia - Efendi; Mahfud; Syahbandir, Mahdi; Alqarni, Wais (International Journal of Criminology and Sociology, 2022)
Law on natural resource management in Indonesia only deals with each sector, which results in a frequent conflict of law between laws in one sector and another. To prevent such conflict, Indonesia requires one comprehensive, integrated, and synergic law regarding the natural resource management in order that each law in this sector does not conflict. In addition, Indonesia also needs to actualize harmonization, revision, and invalidation of law, and even needs to establish new law in natural resource management.